Diagnostic and Therapeutic Challenges in Pregnancy-Associated Breast Cancer: A Literature Review - Michalska, Maria; Kowalik, Kinga; Zielińska, Aleksandra; Tylczyńska, Kinga; Skiba, Jakub; Szypulski, Szymon; Iwaniuk, Sebastian; Maciejewski, Ignacy; Skiba, Zuzanna; Tylczyńska, Natalia (Quality in Sport, 2025)
Introduction: Pregnancy-associated breast cancer (PABC) is an increasingly diagnosed malignancy, typically occurring during pregnancy or within one year postpartum. This review summarizes current knowledge on PABC diagnosis, treatment and clinical management, with attention to both maternal outcomes and fetal safety. Diagnostic: The diagnosis of PABC requires careful consideration of both maternal health and fetal safety. Diagnostic process typically begins with the detection of a palpable mass, followed by ultrasound imaging and biopsy. Mammography and MRI may be used selectively, whereas CT and PET-CT are avoided due to radiation exposure. Physiological changes during pregnancy often delay recognition. Histopathology: Histopathological evaluation of PABC follows standard classifications, including the AJCC TNM and WHO systems, with assessment of ER, PR, HER2, Ki-67, and tumor grade. The most common histological type is ductal infiltrating adenocarcinoma. Treatment: Treatment of PABC is complex and multifactorial, often requiring adjustments to standard protocols to balance effective maternal therapy with fetal safety. Surgery is considered safe during all trimesters, while chemotherapy is typically used in the second and third trimesters. Trastuzumab, tamoxifen, and radiotherapy are generally avoided due to fetal risks, though radiotherapy may be considered in selected cases after thorough evaluation. Conclusion: Pregnancy-associated breast cancer requires an individualized, multidisciplinary approach, with diagnosis and treatment tailored to balance effective maternal care and fetal safety.